1978
DOI: 10.1002/jso.2930100608
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal lymphangioma

Abstract: Mediastinal lymphangioma is an uncommon benign tumor accounting for 0.7 to 4.5% of all mediastinal masses. Lymphangiomas consist of dilated cystic lymph spaces lined by single layers of endothelium and do not undergo malignant change. Most mediastinal lymphangiomas are asymptomatic. There are no specific radiological findings. Surgical excision is the treatment of choice and the prognosis is excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…It was first described by Rodenber in 1828; 65% of lesions are found in children and they do not exhibit any gender predilection 2 , 4 . These constitute 0.7%–4.5% of mediastinal tumours; 5 90% of these tumours manifest as a mass in the neck or axilla in children, and only 10% had internal or visceral locations such as the abdomen or thorax.…”
Section: Discussionmentioning
confidence: 99%
“…It was first described by Rodenber in 1828; 65% of lesions are found in children and they do not exhibit any gender predilection 2 , 4 . These constitute 0.7%–4.5% of mediastinal tumours; 5 90% of these tumours manifest as a mass in the neck or axilla in children, and only 10% had internal or visceral locations such as the abdomen or thorax.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphangiomas are usually found during childhood (mainly less than two years of age), and adult cases are rare [4]. When detected in adults, they are more often mediastinal in location, and are generally asymptomatic [5]. The etiology remains unclear; however, it is suggested that dysembryogenic factors, abdominal trauma, lymphatic obstructions, or a local degeneration of some lymphatic tissues may lead to the formation of such cysts [6].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly affected sites are the cervical and axillary areas. Mediastinal cystic lymphangioma is rare, accounting for 0.7% to 4.5% of all mediastinal tumors [2]. To our knowledge, this is the first report of a case of mediastinal cystic lymphangioma with coexistence of situs inversus totalis.…”
Section: Introductionmentioning
confidence: 99%